Cultural Resistance and Textual Emotionality in the Sahrawi Poetic Anthology VerSahara - Alberto López Martín (Studies in 20th & 21st Century Literature, 2020)
A group of Hispanophone Sahrawi poets founded their own Generación de la Amistad ‘Friendship Generation’ in Madrid in 2005. Ever since, Sahrawi poetry in Spanish has found in the anthology an ideal format to present itself to the Spanish reader, counting more than a dozen publications of poetry collections. Such profusion has nothing to do with the struggle for the cultural hegemony characteristic of other currents within the Spanish poetic field. By contrast, these collections keep to the anthologists’ double logic of cultural preservation and literary activism, which emphasize the communitarian character of their poetry. In this paper, I examine the critical contribution of such double logic to peninsular literary and cultural studies in the anthology VerSahara (Looking at Sahara). In this editorial project, authors from the Canary Islands, one of the seventeen autonomous communities that comprise the Spanish State, and Sahrawi poets share pages and territorial concerns about the political conflict in Western Sahara, which has remained unsolved since the Moroccan occupation in 1975. In particular, I study the production and circulation of emotional attachments between Spanish and Sahrawi poets, and the resulting poetic space of transnational solidarity in dialogue with the colonial discourse of Hispanidad ‘Spanishness’ and human rights’ activism. From this angle, I explore the choice of Spanish as the lingua franca between these communities and the collective praxis present in their writing, characterized by the use of a communal “we” and the inclusion of Hassaniya, the native language of Sahrawi poets. I argue that Sahrawi poetic anthologies in general and VerSahara in particular attempt to consolidate an additional cultural front in the struggle for the recognition of self-determination in Western Sahara. They do so by interpellating the Spanish-speaking community while delving into textual emotional resources that converge in three rhetorical topoi: the Sahrawi people’s resilience in the face of repeated Moroccan aggressions, the romanticizing of their nomadic past, and the linguistic and literary ties with Spain.
Keywords: Sahrawi Hispanophone Poetry; Canarian Poetry; Peninsular Literary and Cultural Studies; Emotion Studies